The Effect Of The Ability In Mastering Dialogue Towards Student’s English Learning Achievement At SMK Negeri 1 Rawamerta Karawang - Asep Darojatul Romli; Sihabudin (BUANA ILMU, 2020)
The effect of the ability in mastering dialogue, to know and explain the effect of the ability in mastering dialogue on English learning achievement, to know and explain the effect of ability on English learning achievement and to know and explain the effect of the ability in mastering dialogue on learning achievement English through motivation. The research method used is survey method. Population in this research is all students of class X of first semester of SMK Negeri 1 Rawamerta, Karawang. The sampling technique used is cluster random sampling, the sample is taken randomly according to the class that has been formed. So, the sample in this study as many as 18 people from the total population of 192 people. The research instrument consists of three types of tests, namely the questionnaire of the ability in mastering dialogue , English achievement test with the subject of the circle. Analysis of statistical data to test the hypothesis in this study using Path Analysis (Path Analysis). Statistic test is used t test. The results showed: (1) direct effect of the ability in mastering dialogue (2) direct effect of the ability in mastering dialogue on English learning achievement, (3) direct effect of the ability in mastering dialogue to English learning achievement and (4) indirect effect of lateral thinking ability toward English learning achievement through creative thinking ability. Keywords: The ability in mastering dialogue, English learning achievement